Effect of temperature on corrosion behavior of E690 steel in 3.5 wt.% NaCl solution - Qi Yan; Qun Yin; Jie Cui; Xinyi Wang; Yanxin Qiao; Huiling Zhou (Materials Research Express, 2021)
The corrosion behavior of E690 steel in 3.5 wt.% NaCl solution at temperatures from 20 °C to 60 °C was investigated using electrochemical test. The corrosion morphology was characterized using SEM and AFM, and the corrosion layer was characterized using EDS, Raman spectroscopy and XPS. The results showed that the corrosion rate of E690 steel improves with the increase in temperature. The corrosion layers of E690 steel are mainly composed of α -Fe _2 O _3 , α -FeOOH and γ -FeOOH. With the elevated temperature, the content of α -FeOOH in corrosion layers increases, while the content of α -Fe _2 O _3 and γ -FeOOH decreases. The corrosion mechanisms were briefly discussed.